The Effect of GA3 and Salicylic Acid Combination on the Growth of Groundnut Sprout (Arachis Hypogaea L.) on Aluminum Stress - Noviani, Noviani; Lande, Martha Lulus; Zulkifli, Zulkifli; Yulianty, Yulianty (Biosfer: Jurnal Tadris Biologi, 2020)
This study aimed to determine the influence of GA3 and salicylic acid on the germination and growth of Kelinci variety groundnut under aluminum stress. The research was conducted in the Botanical Laboratory of the Faculty of Mathematics and Natural Sciences, University of Lampung. This research was conducted in a 2x3 factorial experimental design. Factor A was AL (OH) 3 with two levels of concentration: 0% b/v and 5% b/v. Factor B was Growth Stimulant Substance (ZPT) with three levels of concentration: GA3 (0.1% w/v), salicylic acid (0.1% w/v), and GA3 and salicylic acid. The Tukey test determined the Main Effect, and the Simple Effect was determined with F-test at a significant level of 5%. It can be concluded that the mixture of GA3 solution and US solution was more effective than a single solution of GA3 or US.